Performance Study on Hot Air Recovery for Solar Thermoelectric Cooler System - Zulkipli, Muhammad Shamil (IRC, 2016)
This study presents theoretical and simulation result of thermoelectric heat recovery system, which is used to heat water for household application. As the rise of energy requirements for electric appliances increases, innovation purpose on heat recovery system is practised, specifically in heating water. The numerical and simulation model has been developed by using Simulink/Matlab in order to determine the performance of heat recovery from thermoelectric cooler exhaust.